2009
DOI: 10.1093/aje/kwp220
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific Associations Between Soy and Risk of Hip Fracture in the Singapore Chinese Health Study

Abstract: Although there is some epidemiologic evidence that soy may reduce risk of osteoporotic fracture in women, it is not known whether this risk reduction also occurs for men. The authors examined gender-specific associations between soy intake and hip fracture risk in the Singapore Chinese Health Study, a prospective cohort of 63,257 Chinese living in Singapore. At recruitment between 1993 and 1998, each subject was administered a food frequency questionnaire and questions on medical history and lifestyle factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 42 publications
3
61
1
3
Order By: Relevance
“…Analysis of fracture incidence in the Shanghai cohort (Zhang et al, 2005) and of hip fracture in the Singapore cohort (Koh et al, 2009) shows in both studies one-third reductions in fracture risk when comparing high-with low-soy consumers.…”
Section: Isoflavone and Bone Fracturementioning
confidence: 95%
“…Analysis of fracture incidence in the Shanghai cohort (Zhang et al, 2005) and of hip fracture in the Singapore cohort (Koh et al, 2009) shows in both studies one-third reductions in fracture risk when comparing high-with low-soy consumers.…”
Section: Isoflavone and Bone Fracturementioning
confidence: 95%
“…Both found a reduction in fracture risk for Chinese women [Koh et al 2009;Zhang et al 2005], but a similar result was not observed in Chinese men [Koh et al 2009]. In the Shanghai Women's Health Study, the 24,403 postmenopausal women followed for 4.5 years had 1770 incident fractures (of any type other than fingers, toes, skull, or face).…”
Section: Prospective Studiesmentioning
confidence: 95%
“…There is evidence that early exposure to the bioactive compounds of soybean, via maternal diet, may alter the paracrine signaling in adipocytes of breast tissue and increase the differentiation of epithelial tissue, with implications in prevention of breast cancer associated with obesity (Su et al, 2009). In prostate cancer, the chemopreventive effect of the soybean mediated by mechanisms of modulations of gene expression was evidenced in a study in which isoflavones derived from soybean cake exhibited antiproliferative effects on prostate cancer cells, decreasing the expression of cyclin B1 (Wang et al, 2009). A recent study investigated the effect of administration of soy isoflavones as an adjunct in hormone therapy and verified that for postmenopausal women there was lower risk of cancer recurrence, for a monitoring period of 5.1 years .…”
Section: Chemopreventive Effectsmentioning
confidence: 99%
“…A prospective cohort study of the Chinese population showed that the intake of soybean and its products was associated with protection against hip fracture in women but no association in men (Koh et al, 2009). There are doubts if the intake of soybean can provide superior beneficial effect on bone health .…”
Section: Other Diverse Effectsmentioning
confidence: 99%